The Influence E-Service Quality and Complain Handling BSI Mobile on Customer Satisfaction - Bella Shafiera Anandita; Agus Rahayu; Puspo Dewi Dirgantari (Journal of Accounting and Finance Management, 2023)
This study aims for know the influence of e-service quality and complaint handling of BSI Mobile banking on satisfaction office BSI customers Asia Afrika branch, Bandung. Type research conducted is study associative causal. This study conducted at Bank BSI Asia Afrika branch which is located at JL. Asia Afrika No. 107, City of Bandung. Data used in study this is the primary data collected through questionnaire. The sample used in study this are 30 customers of BSI Asia Africa. Deep data analysis techniques study this is analysis multiple linear regression with use IBM SPSS version 25 software assistance. Research results this disclose that good in a manner Partial nor simultaneous there is positive and significant influence from e-service quality and complaint handling on satisfaction customers of Bank BSI Asia Afrika branch, Bandung.